Chemotherapy and radiation therapy elicits tumor specific T cell responses in a breast cancer patient. Issue 1 (December 2016) - Bernal-Estévez, David; Sánchez, Ramiro; Tejada, Rafael; Parra-López, Carlos
Abstract Background Experimental evidence and clinical studies in breast cancer suggest that some anti-tumor therapy regimens generate stimulation of the immune system that accounts for tumor clinical responses, however, demonstration of the immunostimulatory power of these therapies on cancer patients continues to be a formidable challenge. Here we present experimental evidence from a breast cancer patient with complete clinical response after 7 years, associated with responsiveness of tumor specific T cells. Methods T cells were obtained before and after anti-tumor therapy from peripheral blood of a 63-years old woman diagnosed with ductal breast cancer (HER2/neu+++, ER-, PR-, HLA-A*02:01) treated with surgery, followed by paclitaxel, trastuzumab (suspended due to cardiac toxicity), and radiotherapy. We obtained a leukapheresis before surgery and after 8 months of treatment. Using in vitro cell cultures stimulated with autologous monocyte-derived dendritic cells (DCs) that produce high levels of IL-12, we characterize by flow cytometry the phenotype of tumor associated antigens (TAAs) HER2/neu and NY-ESO 1 specific T cells. The ex vivo analysis of the TCR-Vβ repertoire of TAA specific T cells in blood and Tumor Infiltrating Lymphocytes (TILs) were performed in order to correlate both repertoires prior and after therapy. Results We evidence a functional recovery of T cell responsiveness to polyclonal stimuli and expansion of TAAs specific CD8+ T cells using peptide pulsed DCs, with an increase of CTLA-4 and memory effector phenotype after anti-tumor therapy. The ex vivo analysis of the TCR-Vβ repertoire of TAA specific T cells in blood and TILs showed that whereas the TCR-Vβ04-02 clonotype is highly expressed in TILs the HER2/neu specific T cells are expressed mainly in blood after therapy, suggesting that this particular TCR was selectively enriched in blood after anti-tumor therapy. Conclusions Our results show the benefits of anti-tumor therapy in a breast cancer patient with clinical complete response in two ways, by restoring the responsiveness of T cells by increasing the frequency and activation in peripheral blood of tumor specific T cells present in the tumor before therapy.